Identification of Growth-Associated Genes by Genome-Wide Association Study and Their Potential Application in the Breeding of Pacific White Shrimp (Litopenaeus vannamei) - Lyu, Ding; Yu, Yang; Wang, Quanchao; Luo, Zheng; Zhang, Qian; Zhang, Xiaojun; Xiang, Jianhai; Li, Fuhua (Frontiers in Genetics, 2021)
Pacific white shrimp (Litopenaeus vannamei) is the most widely cultured shrimp in the world. A great attention has been paid to improve its body weight (BW) at harvest through genetic selection for decades. Genome-wide association study (GWAS) is a tool to dissect the genetic basis of the traits. In this study, a GWAS approach was conducted to find genes related to BW through genotyping 94,113 SNPs in 200 individuals from a breeding population. Four BW related SNPs, locating in LG19 and LG39 were identified. Through further candidate gene association analysis, the SNPs in two candidate genes, deoxycytidylate deaminase and non-receptor protein tyrosine kinase, were found to be related with body weight of the shrimp. Marker assisted BLUP (MA-BLUP) based on the SNPs in these two genes were used to estimate the breeding values, and the result showed that the highest prediction accuracy of MA-BLUP was 9.4% increased than traditional BLUP. These results will provide useful information for the marker-assisted breeding in L. vannamei.